2019 16th International Conference on the European Energy Market (EEM) 2019
DOI: 10.1109/eem.2019.8916377
|View full text |Cite
|
Sign up to set email alerts
|

Modelling TSO-DSO coordination: The value of distributed flexible resources to the power system

Abstract: The interaction between the transmission and distribution system operators is mainly based on a unidirectional flow of information (transmission-to-distribution system operators). The resources in the distribution systems are, hence, not utilized fully in overall power system operations, regardless that they may serve as sources of flexibility to manage renewable energy sources fluctuations. In the existing literature, is not very clear how the coordination of the transmission and distribution system operators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Results of the case studies conducted as demonstrated on a section of Great Britain distribution network using high DER growth scenario data for the year 2030, show that the proposed approach is able to maintain thermal and voltage limits during periods of peak demand and DER output. In Grøttum et al (2019), a multiobjective optimization method TSO-DSO coordination with flexibility supplied by DERs is proposed, where the flexibility is obtained by minimizing the overall cost of power system operations as well as the impact of including the cost across the two levels in the coordinated power system. Results indicate that the conflicting interests of the TSO and the DSOs can be considered using the proposed multiobjective optimization method.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the case studies conducted as demonstrated on a section of Great Britain distribution network using high DER growth scenario data for the year 2030, show that the proposed approach is able to maintain thermal and voltage limits during periods of peak demand and DER output. In Grøttum et al (2019), a multiobjective optimization method TSO-DSO coordination with flexibility supplied by DERs is proposed, where the flexibility is obtained by minimizing the overall cost of power system operations as well as the impact of including the cost across the two levels in the coordinated power system. Results indicate that the conflicting interests of the TSO and the DSOs can be considered using the proposed multiobjective optimization method.…”
Section: Introductionmentioning
confidence: 99%
“…ISOs currently lack control systems that can deal with the shift from tens of generators that were located on the transmission system towards one that has a very large number of small inverter-connected rooftop PV systems generating significant portions of the energy from within the distribution system. This will require improved coordination between the distribution system and transmission system operation [26] and the development of automated control mechanisms [90].…”
Section: Technical Aspectsmentioning
confidence: 99%
“…In the case of rooftop PV, much of this change is being exerted upon the incumbent regime by their traditional customers and is requiring substantial infrastructure augmentation to be financed, designed, built and made operational within time periods ranging from months to years [19]. Rooftop PV generation is also being built in an unplanned manner across the distribution system, rather than through the centrally controlled transmission system [26]. This duality combines to represent a fundamental reconfiguration of the relationship between markets, electricity consumption and production patterns and electricity transportation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem ( 24)-( 27) is mixed-integer nonlinear programming (MINLP) problem, which is difficult in view of the combinatorial complexity introduced by binary unit commitment variables within generation capacity (2)-(3) and ramprate constraints (4)- (7), and the non-linearity introduced by AC power flow (10)-(11), voltage restrictions (12)-( 13), transmission capacity constraints (14) and the interface power flow restrictions (27). Moreover, cross-product terms within AC power flows (10)- (11) and voltage restrictions (12) contribute to the non-convexity of the problem.…”
Section: Coordinated Tso-dso Modelmentioning
confidence: 99%
“…also they are expected to provide support for the TSO [11]- [15]. Flexibility benefits benefits enabled by DERs [1], [2], [5]- [7], [11], [16], [17], [21]- [23], which include balancing supply and demand, and voltage control [2], [16], [17], voltage fluctuation and congestion mitigation [21], as well as prosumer behavior of customers [1], can be achieved. The cost-benefits have also been discussed in [18]- [20].…”
mentioning
confidence: 99%